2021
DOI: 10.1186/s13048-021-00794-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential markers for differentiating epithelial ovarian cancer from ovarian low malignant potential tumors through integrated bioinformatics analysis

Abstract: Background Epithelial ovarian cancer (EOC), as a lethal malignancy in women, is often diagnosed as advanced stages. In contrast, intermediating between benign and malignant tumors, ovarian low malignant potential (LMP) tumors show a good prognosis. However, the differential diagnosis of the two diseases is not ideal, resulting in delays or unnecessary therapies. Therefore, unveiling the molecular differences between LMP and EOC may contribute to differential diagnosis and novel therapeutic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…It is important to note that kinesins play an important regulatory role in the formation of spindles, separation of chromosomes, and cytokinesis, and in the case of abnormal expression/function of kinesins, daughter cells become aneuploidic, thereby resulting in tumorigenesis [57]. In particular, elevated levels of KIF23 have been associated with adverse outcomes in ovarian, breast, and lung cancers [58][59][60]. MiR-125b-5p may serve as a platinum-chemoresistance marker, as its downregulation was observed in tumorspheres derived from the SKOV-3 platinum-resistant cell line [61].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that kinesins play an important regulatory role in the formation of spindles, separation of chromosomes, and cytokinesis, and in the case of abnormal expression/function of kinesins, daughter cells become aneuploidic, thereby resulting in tumorigenesis [57]. In particular, elevated levels of KIF23 have been associated with adverse outcomes in ovarian, breast, and lung cancers [58][59][60]. MiR-125b-5p may serve as a platinum-chemoresistance marker, as its downregulation was observed in tumorspheres derived from the SKOV-3 platinum-resistant cell line [61].…”
Section: Discussionmentioning
confidence: 99%
“…Also, TIDE scores were higher in the high-risk group than in the low-risk group. TIDE is a computational platform for immunotherapy prediction, and its predictive capabilities have been demonstrated in many cancers with great success [30][31][32][33]. ese results suggest that patients in the high-risk group have a higher response rate to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that ASPM is abnormally expressed in various cancers and could predict prognosis in several types, including glioblastoma (8), endometrial adenocarcinoma (9), pancreatic carcinoma (10), and prostate adenocarcinoma (11). Based on integrated bioinformatics analysis, 2 studies identified ASPM as a potential biomarker and drug target for EOC (12,13). Brüning-Richardson et al found ASPM was highly expressed in primary ovarian cultures, and the higher the grade, the higher its expression (14).…”
Section: Introductionmentioning
confidence: 99%